ANALISIS INTELLECTUAL CAPITAL TERHADAP KINERJA BUMN - Adi Wiratno; Sukirman - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2012)
This study is an empirical research on state-owned enterprises under the title IntellectualCapital Analysis of the Performance of State Owned Enterprises, which aims to: (a) In order to testempirically the influence of intellectual capital (VAIC) of market value (M / B), (b) To test empiricallythe effect intellectual capital (VAIC) to profitability (ROE). (c) in order to test empirically the influenceof intellectual capital (VAIC) on the growth of revenue (GR). the sample was selected by purposivesampling as much as 7 companies. The data used in the form of soft copy of the financial statementsstatse-owned companies from 2007 until 2010 which have been audited and published. Thisresearch uses analysis tool Partial Least Square (PLS). Based on the research results can beconcluded that:1. Intellectual capital (VAIC) proved to affect the market value (M / B).2. Intellectual capital (VAIC) proved to affect the profitability (ROE).3. Intellectual capital (VAIC) proved influential on the growth of revenue (GR).Investments in intellectual capital to be one alternative that can be done by the company toincrease the market value of profitability, and growth rate. Enterprises need to improve efficiency inthe management of physical capital, improve the competence of employees and create efficienciesin routine operational processes of the company.